Method of theory based impact evaluation applied to policy conducive to climate smart agriculture scaling - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The method has been applied to the EASAC, the method has been applied in two phases: 1) the definition of the theory of change of EASAC policy and identification of changes, and 2) the contribution evaluation of the policy to selected changes.